2018
DOI: 10.1111/iej.12995
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of technology‐enhanced learning in Endodontic education: a systematic review and meta‐analysis

Abstract: The aim of the present systematic review was to evaluate the effectiveness of technology-enhanced learning (TEL) in the field of Endodontics to improve educational outcomes compared to traditional learning methods. Randomized controlled studies published in English were identified from two electronic databases (PubMed and Scopus) up to May 2018. Two authors independently performed study selection, data extraction and assessed the risk of bias (ROB). Any teaching method using TEL was considered as the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 31 publications
(71 reference statements)
4
57
0
Order By: Relevance
“…In a recent systematic review and meta‐analysis, Nagendrababu et al . () reported that the effectiveness of technology‐enhanced learning was comparable to that of traditional learning methods. From this, it is clear that the search for an enhancement in teaching methods should incorporate recent advances in technology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent systematic review and meta‐analysis, Nagendrababu et al . () reported that the effectiveness of technology‐enhanced learning was comparable to that of traditional learning methods. From this, it is clear that the search for an enhancement in teaching methods should incorporate recent advances in technology.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, information technology has modernized certain aspects of education (Qualtrough 2014), whilst haptic virtual reality (Suebnukarn et al 2011) and videoassisted clinical instruction (Naseri et al 2016) are emerging as alternative educational methods in endodontics. In a recent systematic review and metaanalysis, Nagendrababu et al (2019) reported that the effectiveness of technology-enhanced learning was comparable to that of traditional learning methods. From this, it is clear that the search for an enhancement in teaching methods should incorporate recent advances in technology.…”
Section: Discussionmentioning
confidence: 99%
“…). Example 1b : ‘Effectiveness of technology‐enhanced learning in Endodontic education: a systematic review and meta‐analysis’ (Nagendrababu et al . 2019a). Example 1c : ‘Single‐visit or multiple‐visit root canal treatment: systematic review, meta‐analysis and trial sequential analysis’ (Schwendicke & Göstemeyer ). Example 1d : ‘Efficacy of local anaesthetic solutions on the success of inferior alveolar nerve block in patients with irreversible pulpitis: A systematic review and network meta‐analysis of randomized clinical trials’ (Nagendrababu et al .…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 99%
“…Example 1b : ‘Effectiveness of technology‐enhanced learning in Endodontic education: a systematic review and meta‐analysis’ (Nagendrababu et al . 2019a).…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 99%
See 1 more Smart Citation